SEKATEN: A STUDY ON THE VALUES AND RELATIONSHIPS OF GOD, THE UNIVERSE, AND SOCIETY IN YOGYAKARTA - Putra, Aqiel; Apriyanto, Dwi; Waly, Muchamad Muchibbuddin (West Science Islamic Studies, 2026)
This research examines the process of spreading Islam through Sekaten and the orientation of Javanese cultural values embedded in Yogyakarta. The process of Islamization in this context is closely linked to the role of the Walisongo, who facilitated the inclusive integration of Islam through traditions and culture, allowing it to endure to this day. Sekati, or gamelan music, was used as a medium for Islamization. This tradition later evolved into what is now known as Sekaten, which remains a preserved cultural heritage. The term Sekaten is derived from Syahadatain, meaning the two Islamic declarations of faith. However, Sekaten has evolved beyond a tool for Islamization and has become a means of entertainment and a source of economic support for the community. The research adopts a descriptive method with description, interpretation, heuristics, and critical reflection from a philosophical, qualitative perspective. It draws on sources such as journals, books, news articles, and other literature. The positive impacts of Sekaten on the relationship between God, the universe, and society, as analyzed through the relevant theories, include an inclusive renewal of the Islamization process, the preservation of culture, and the fostering of moral values in society.